RISIKO PENGGUNAAN DANA SEBAGAI DOMPET DIGITAL: STUDI PERSEPSI MAHASISWA PENDIDIKAN EKONOMI - Lira Septia Zahra; Anisa Triana Octavia; Nazwa Rahmawati; Firda Fitriyanti; Cepri Maulana (Jurnal Bina Bangsa Ekonomika, 2024)
Technological developments are undergoing dynamic changes. Digital wallet (e-wallet) as a transaction tool is one that is affected by technological developments. The use of this digital wallet does not mean without risk. This study aims to describe the perceptions of Economics Education Students Class of 2023 on the issues and risks of using the DANA application. The method used in this research is descriptive qualitative with a case study approach. The data collection technique used was interviews with 30 sources. The subjects of this research are students of Economics Education Class of 2023, University of Education Indonesia. The results of this study indicate that the factor that causes user loyalty to the DANA application is a sense of comfort that creates strong trust for users. Although the issues and risks of using DANA are quite high, the data proves that users can accept the risks followed by an attitude of vigilance about the threats that can occur